UBAID CERAMIC PRODUCTION IN THE HILLY FLANKS OF NORTHWESTERN POSHT-I KUH (ILAM - WEST IRAN). (25th September 2018) - Mazaheri, Khoda Karam
Abstract : This paper examines discoveries made during the survey of Kall Karim and presents a chronological framework for this site based on ceramic decorative styles and forms. This site was first identified during archaeological survey of the northwestern part of the Posht-i Kuh area in Ilam province (west Iran) in the winter of 2016. Kall Karim is located in a rugged area on the northern slopes of Seh Kurvand Mountain in the Bawlly region, which is used for winter pastures of nomadic tribes. According to surface remains, the ancient use of Kall Karim is entirely related to pottery production activities. All the surface sherds belong to the Ubaid period; according to typological studies and comparison of motifs and forms, we propose that Kall Karim belongs to Ubaid 2-3. It seems that both abundance of necessary materials and the accessibility of fuel for kilns caused the formation of Kall Karim in this location, far from residential centers.